Shame and guilt in the suicidality related to traumatic events: A systematic literature review - Ollivier, Flavie; Soubelet, Andréa; Duhem, Stéphane; Thümmler, Susanne (Frontiers in Psychiatry, 2022)
Background: Shame and guilt are involved in suicidality and in post-traumatic stress disorder. However, few studies have explored the implication of those emotions in the suicidality of patients exposed to traumatic events. Objective: The objective of this literature review was to examine the implication of shame and guilt in the suicidality of individuals who have experienced potentially traumatic events or been diagnosed with post-traumatic stress disorder. These two emotions are part of post-traumatic stress disorder and suicidality. Moreover, when individuals perceive that their coping strategies are inadequate, they may view suicide as a relief from suffering. Method: This review was conducted according to PRISMA method. We used combinations of search words for traumatisation, suicide ideation and behavior and shame and guilt to search for empirical studies in common databases in psychology and medicine. Results: Among 137 identified articles, 9 full texts were retained. Results suggest that shame and guilt were involved in all aspects of suicidality in patients who had experienced traumatic events or been diagnosed with post-traumatic stress disorder. The degree of shame and guilt differed with the type of traumatic event, notably affecting individuals who had experienced military combat, physical or sexual abuse, or emotional or physical neglect. Conclusion: Shame and guilt are implicated in suicide’s risk. Future research is now needed to determine whether greater attention to these two emotions would enhance our understanding and anticipation of suicidal behavior in those who have experienced a potentially traumatic event or been diagnosed with post-traumatic stress disorder.